Visualization in Science Education
XXXIX, 346 p.
Keywords: Visualization, meaning both the perception of an object that is seen or touched and the mental imagery that is the product of that perception, is believed to be a major strategy in all thought. It is particularly important in science, which seeks causal explanations for phenomena in the world-as-experienced. Visualization must therefore play a major role in science education. This book addresses key issues concerning visualization in the teaching and learning of science at any level in educational systems. ‘Visualization in Science Education’ draws on the insights from cognitive psychology, science, and education, by experts from Australia, Israel, Slovenia, UK, and USA. It unites these with the practice of science education, particularly the ever-increasing use of computer-managed modelling packages, especially in chemistry. The first section explores the significance and intellectual standing of visualization. The second section shows how the skills of visualization have been developed practically in science education. This is followed by accounts of how the educational value of visualization has been integrated into university courses in physics, genomics, and geology. The fourth section documents experimental work on the classroom assessment of visualization. An endpiece summarises some of the research and development needed if the contribution of this set of universal skills is to be fully exploited at all levels and in all science subjects.